Penerapan Model Pembelajaran Jigsaw untuk Meningkatkan Kemampuan Membaca Siswa Kelas IX SMP Negeri 26 Makassar - Ainun, Nur; Mayong, Mayong; Nurhusna, Nurhusna (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the planning, implementation, and learning outcomes of ninth-grade students of SMP Negeri 26 Makassar in understanding the content of short stories through the application of the Jigsaw learning model. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data collection techniques include observation to observe student activities and involvement during the learning process, tests conducted before and after learning to measure the increase in student understanding of the content of short stories, questionnaires to collect student responses regarding the effectiveness of the Jigsaw model application, and documentation as complementary data to support the validity of the research results. Data from observations, questionnaires, and documentation were analyzed qualitatively, while test data were analyzed quantitatively using the average value and the Minimum Completion Criteria (KKM) as a reference. The results of the study showed that there was a significant increase in students' reading ability. In cycle I, the average value of student learning outcomes was 67.67, still below the specified KKM of 75. After improvements and strengthening strategies were made in cycle II, the average value increased to 80.17. This indicates that the Jigsaw learning model is effective in improving the reading skills of ninth-grade students at SMP Negeri 26 Makassar, particularly in understanding the content of short stories.